Concepts of Finnish Education: African Student Teacher Reflections at the Cultural Cross-Roads - Somerkoski Brita; Granö Päivi (Nova Science Publishers, Inc., 2022)
The aim of this research was to study international students´ learning experiences and the concepts they are using when describing Finnish comprehensive school. The study is based on the observation portfolios of 23 international student teachers during the first term of their undergraduate studies in Finland. The results indicate, that the student teachers describe their early school years in their homeland in terms of educational ranking, the connection and influence of relatives, disciplines, control, and authorities. Their reflections of the Finnish school system, based on their observation reports, were connected to three main concepts – individuality, equality and freedom.
Education Curriculum Development: Perspectives, Challenges and Future Directions